COMPARISON BETWEEN STUDENT SCORES IN MULTIPLE CHOICE QUESTIONS AND STRUCTURED ESSAY QUESTIONS AT III MBBS EXAMINATION IN OTORHINOLARYNGOLOGY IN A MEDICAL COLLEGE IN MAURITIUS - HS SHARMA,; MM MUTALIK, (International Journal of Pharma and Bio Sciences, 2014)
Student evaluation is done by various methods like a multiple choice question (MCQ), Essay questions, Structured essay question (SEQ), Modified essay question (MEQ), Objective structured clinical assessment (OSCE) in assessment of MBBS students in various universities worldwide. The present retrospective study compared the student performance in single-response MCQs and SEQs in the subject of otorhinolaryngology at the III MBBS examination at SSR Medical College, Mauritius. Performance of 639 students was analyzed over a period of 6 years, using SPSS-16 software. Scores in SEQs averaged at 47.63% (SD 11.90), while those in MCQs averaged at 55.24% (SD 17.90). MCQ scores were significantly higher than the SEQ scores when analyzed by two-way ANOVA. Pearson correlation between SEQ and MCQ scores was strongly significant indicating the performance to be independent of the type of questioning. Analysis of the scores of top-20% scorers (n=128) and bottom-20% scorers (n=128) did not show significant correlation.